2019
DOI: 10.21608/ebwhj.2019.33486
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bilateral total salpingectomy versus standard tubal ligation at time of cesarean section on ovarian reserve: A randomized controlled trial

Abstract: Aim of the work: The objective of this trial was to compare between bilateral total salpingectomy (BTS) as a theoretically more effective ovarian cancer (OvCa) risk-reducing primary prevention and bilateral partial salpingectomy (BPS) [stander tubal ligation (STL)] procedures at time of cesarean section (CS) for parturients who completed their reproductive desire and requesting permanent sterilization regard to the impacts of both procedures on ovarian reserve parameters at one year post-sterilization as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A triad-center clinical trial compared the effect of bilateral salpingectomy with a bipolar device and bilateral partial salpingectomy on ovarian reserve in women undergoing cesarean delivery after one year. The results showed no significant differences between the two procedures in terms of hormonal (AMH and FSH) and ultrasonographic (PSV, AFC, VI, FI, ovarian volume, and calculated ovarian age) parameters [66]. In another randomized trial, the measurement of AMH levels before and six-eight weeks postdelivery in women who underwent salpingectomy via monopolar electrosurgery or tubal ligation using the Parkland method during C-section showed no significant difference either within or between groups [67].…”
Section: Ovarian Reservementioning
confidence: 86%
“…A triad-center clinical trial compared the effect of bilateral salpingectomy with a bipolar device and bilateral partial salpingectomy on ovarian reserve in women undergoing cesarean delivery after one year. The results showed no significant differences between the two procedures in terms of hormonal (AMH and FSH) and ultrasonographic (PSV, AFC, VI, FI, ovarian volume, and calculated ovarian age) parameters [66]. In another randomized trial, the measurement of AMH levels before and six-eight weeks postdelivery in women who underwent salpingectomy via monopolar electrosurgery or tubal ligation using the Parkland method during C-section showed no significant difference either within or between groups [67].…”
Section: Ovarian Reservementioning
confidence: 86%
“…With the pathology data available, it has been demonstrated that up to 70% of ovarian cancers originate from the fallopian tubes. A study conducted in Sweden between 1973 and 2009 demonstrated that 251,465 women who underwent bilateral salpingo-oophorectomy for benign reasons during gynecological surgery had a lower risk of ovarian cancer than those who underwent BTL [24]. In the study, which lasted for about 14 years and had a considerably high number of cases (1,132,914 patients), TS was performed in 264,048 patients.…”
Section: Discussionmentioning
confidence: 99%